Development of an innovative microwave assisted food freezing process - Xanthakis, Epameinondas; LeBail, Alain; Ramaswamy, Hosahalli Swamy (My University, 2014)
In this study, a novel experimental setup was developed and an innovative process was implemented aiming at the application of microwave radiation during freezing of a food matrix. The results acquired from the present study are considered as remarkable and promising. The developed freezing process was applied on pork tenderloin samples. The application of microwaves during cooling the samples caused oscillated decrease of temperature and had a significant impact on the crystallization process as the degree of supercooling was decreased circa 92% under the tested conditions. The meat microstructure evaluation showed a 62% decrease in the average ice crystal size when samples were frozen under a microwave field as compared to the conventional freezing process. These results indicate that the application of microwave radiation during freezing may reduce the damage of the meat tissue and in turn to retain better texture in the frozen meat. Industrial relevance The reduction of freeze damage exerted to any tissue undergoing freezing remains a challenge. The mechanical and biochemical stress caused by the ice crystals to the cellular membranes results in irreversible tissue damage. The application of electric and/or magnetic disturbances has been identified as a possible means to reduce the size of ice crystals during freezing of biological tissues. In the present study microwaves were applied during freezing of pork meat. Our results indicate that the size of the formed ice crystals was significantly reduced during microwave assisted freezing leading to a lower damage on the microstructure of meat. This paper describes an innovative and novel freezing process that could be used in order for higher quality frozen products to be produced.
Keywords: Microwave; Freezing; Meat; Microstructure